Public sector financial management - Coombs, Hugh M. (The Chapman & Hall series in accounting and finance, 1991)
In the light of increasing emphasis in the public sector on economy and efficiency, this work covers financial management techniques for service managers. The main aim is to enable them to interpret the financial results. Included are examples and questions for calculation and interpretation